Sorption kinetics and intrapaticulate diffusivity of As(III) bioremediation from aqueous solution, using modified and unmodified coconut fiber - Igwe, Jude Chibuzo; Augustine, Augustina (Eclética Química, 2006)
The pollution and toxicity problems posed by arsenic in the environment have long been established. Hence, the removal and recovery remedies have been sought, bearing in mind the effi- ciency, cost effectiveness and environmental friendliness of the methods employed. The sorption kinet- ics and intraparticulate diffusivity of As (III) bioremediation from aqueous solution using modified and unmodified coconut fiber was investigated. The amount adsorbed increased as time increased, reach- ing equilibrium at about 60 minutes. The kinetic studies showed that the sorption rates could be described by both pseudo-first order and pseudo-second order process with the later showing a better fit with a value of rate constant of 1.16 x 10 -4 min -1 for the three adsorbent types. The mechanism of sorption was found to be particle diffusion controlled. The diffusion and boundary layer effects were also investigation. Therefore, the results show that coconut fiber, both modified and unmodified is an efficient sorbent for the removal of As (III) from industrial effluents with particle diffusion as the pre- dominant mechanism.